Waste Management Design for Green Campus - Nina Lestari (Universitas Negeri Padang, 2019)
Academic community activities on campus certainly produce various types of waste, especially paper, plastic bottles, batteries, and various other types of waste. 18% of all criteria Green Campus Criteria according to UI Greenmetric is waste management. Based on the criteria, the campus needs to be focused on the waste management system such as waste segregation, pre-recycling, recycling, organic waste management, and policies on waste management at the university governance to reduce the use of paper and plastic packaging. Technology can be used to improve waste management systems, preparation for recycling waste by crushing it before recycling, collection and transfer of waste to landfill, or organic waste composers around the campus. Various sensors and alarm systems are integrated into waste collection equipment and can be connected through the Internet of Things (IoT) system to be monitored by the authorities. Through the design of a technology-based waste management system, it is hoped that it can reduce waste production for the environment and can increase Green Campus rank which certainly provides positive benefits for the environment, the academic community, and society